Development of a new n-dodecane-n-butanol-PAH reduced mechanism and the applications under diesel spray combustion - Choo, Edwin Jia Chiet (2023)
Despite exhibiting low throttling losses and generating high thermal efficiency, it is inevitable that the heterogeneous combustion nature of a diesel engine will cause large amount of soot to be produced. Lately, n-butanol has emerged as a very competitive second-generation biofuel in diesel engine because of its similarities in physiochemical properties to diesel fuel. As an oxygenated hydrocarbon, blending n-butanol with diesel is able to reduce the harmful exhaust emissions. According to the literature, most studies related to diesel-n-butanol are conducted experimentally whereas only a handful of them are done numerically. However, numerical modelling is as important as conducting experiments as it allows researchers to gain further insights on the chemical kinetics. In order to support accurate combustion modelling results, the selection of a chemical kinetic mechanism that could describe the combustion chemistry precisely is crucial but it is found that the developments of diesel-n-butanol mechanisms in particular those using long carbon chain surrogates are still scarce. Since there is also a lack in effort on the combustion modelling of diesel-n-butanol, this study aims to address the limitations related to the chemical kinetic mechanisms for diesel-n-butanol and the applications in multi-dimensional simulations concerning the spray combustion.